Influence of gold nanoparticles on human fibroblast before and after cryopreservation - Pavlovich, EV; Volkova, NA (Springer International Publishing, 2015)
The aim of our research was to study the influence of gold nanoparticles (AuNPs) on morphological and functional characteristics of the human fibroblast cells before and after cryopreservation. The effect of AuNPs on the viability, proliferative capacity, and apoptosis/necrosis processes of human fibroblast cells was studied. A stimulating effect of AuNPs at concentration of 6 μg/mL on the proliferative ability of fibroblast cells was shown. The results obtained by flow cytometry suggested that AuNPs at concentrations of 1.5 and 3 μg/mL by culturing for 7 days do not cause the development of necrosis and apoptosis in fibroblast cells. After 7 days culturing of the fibroblasts, cryopreserved in the presence of AuNPs at concentration of 6 μg/mL, a decrease in the percentage of viable cells and an increase of the number of apoptotic cells compared with the control samples were observed.
Keywords: Cells Culture Fibroblasts Gold nanoparticles Apoptosis Necrosis Cytofluorimetry Culturing Adhesion Proliferation In vitro Light microscopy 7-AAD Annexin Stimulation Inhibition Suspension